THE INFLUENCE OF PRODUCT QUALITY AND HEDONIC SHOPPING MOTIVES ON CONSUMER LOYALTY FOR WOMEN'S CLOTHING PRODUCTS PARISSA BRAND PANTS AT ROBINSONDEPARTMENT STORE MALUKU CITY MALL - Wendy Souisa; Grace H. Tahapary (Jurnal Ekonomi, 2023)
This research aims to determine the influence of product quality and hedonic shopping motives on consumer loyalty for Parissa brand women's clothing products at Robinson Department Store Maluku City Mall. The population in this study was 100 consumers of Parissa brand women's clothing at Robinson Department Store Maluku City Mall. By using Hair calculations, the sample used in this research was 100. The data collection technique was by administering questionnaires to respondents. Data were analyzed using validity, reliability, classical assumption tests, normality tests, multicollinearity tests, heteroscedasticity tests. The data analysis technique used to test the hypothesis is multiple regression. Based on data analysis, the results of this research show that: Product Quality has a significant effect on Consumer Loyalty, as evidenced by the coefficient value of -0.344. The Sig of 0.000 is smaller than 0.05. Hedonic shopping motives have a significant effect on consumer loyalty, as evidenced by a coefficient value of 0.382. A Sig of 0.000 is greater than 0.05.